2016
DOI: 10.1080/13598139.2016.1212702
|View full text |Cite
|
Sign up to set email alerts
|

Two studies of the empirical basis of two learning resource-oriented motivational strategies for gifted educators

Abstract: Two learning resource-oriented motivational strategies for gifted educators are introduced: a homeostatic orientation that aims for balance and an allostatic orientation that aims at growth. In order to establish the empirical basis of these motivational strategies, two studies were conducted with samples of students from a specialized post-secondary business school who were enrolled in grades 11-13. Study 1 focused on the empirical basis of the homeostatic orientation. It was shown that the availability of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…As systemic gifted education is yet in its nascent stage, many theoretical insights still await being put into practice, and this raises all manner of practical issues. For example, whereas a multitude of IQ tests has been developed and used for gifted education, only two measurement tools are available for measuring the learning resources of the gifted (Harder, Trottler, Vialle, & Ziegler, 2015; Vladut, Vialle, & Ziegler, 2016). Thus, educational provisions, identification tools, and practitioners of gifted education rooted in systems thinking are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…As systemic gifted education is yet in its nascent stage, many theoretical insights still await being put into practice, and this raises all manner of practical issues. For example, whereas a multitude of IQ tests has been developed and used for gifted education, only two measurement tools are available for measuring the learning resources of the gifted (Harder, Trottler, Vialle, & Ziegler, 2015; Vladut, Vialle, & Ziegler, 2016). Thus, educational provisions, identification tools, and practitioners of gifted education rooted in systems thinking are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Resources and capital can be regarded as means to attain a goal (Vladut et al, 2016) or as diverse assets that are used and activated across different fields (Bourdieu, 1986;Moore, 2008) and that enhance the power of an individual. Special attention was given to the resources available to gifted children.…”
Section: Resources For the Giftedmentioning
confidence: 99%
“…Exogenous resources—or educational capital (Ziegler & Baker, 2013)—are located in the environment of gifted children and demonstrate a constant exchange of matter, energy, and information between the child and their environment. Like the context-dependent notion of capital (Lareau et al, 2016; Schneidhofer et al, 2015), exogenous resources function as relational constructs that can be changed according to parents’ preferences or tendencies (Paz-Baruch, 2017; Vladut et al, 2016); they were found to be associated with greater robustness and resilience (Vladut et al, 2016). Ziegler et al (2017) claimed that educators of gifted students should have these resources available at all points on the learning pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have considered types of secondary schooling and students’ educational and learning capital (for an overview, see Harder, Stoeger, & Ziegler, 2013; also see Harder, Trottler, Vialle, & Ziegler, 2015; Vladut, Vialle, & Ziegler, 2016). An exception is Ziegler et al (2011), in which teachers from the three tracks of German secondary schooling were surveyed about their pupils’ educational and learning capital.…”
Section: Educational and Learning Capital: Relations To Type Of Seconmentioning
confidence: 99%